2018
DOI: 10.3390/fermentation4020022
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Strains of Torulaspora delbrueckii Isolated from the Honey Bee Microbiome and Their Use in Honey Fermentation

Abstract: Yeasts are ubiquitous microbes found in virtually all environments. Many yeast species can ferment sugar into ethanol and CO 2 , and humans have taken advantage of these characteristics to produce fermented beverages for thousands of years. As a naturally abundant source of fermentable sugar, honey has had a central role in such fermentations since Neolithic times. However, as beverage fermentation has become industrialized, the processes have been streamlined, including the narrow and almost exclusive usage o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This supports an earlier report that maltose fermentation was variable amongst different strains of T. delbrueckii , because not all strains possessed a maltose transporter and were able to synthesise maltase (Canonico et al , ). Similarly, wort fermentation in a previous study also revealed an extremely poor attenuation of maltose by T. delbrueckii YH178 and YH179, both of which eventually reached an alcohol content of approximately 0.3% (v/v) after 2 weeks of fermentation (Barry et al , ). In addition, the estimated ethanol contents based on the decreases in °Brix were significantly greater in Prelude (3.78, v/v) and Concerto (3.82, v/v)‐fermented beers than that of Biodiva‐fermented beers (1.33, v/v) (Table ).…”
Section: Ph Total Soluble Solids and Sugar Changes During Fermentationmentioning
confidence: 56%
“…This supports an earlier report that maltose fermentation was variable amongst different strains of T. delbrueckii , because not all strains possessed a maltose transporter and were able to synthesise maltase (Canonico et al , ). Similarly, wort fermentation in a previous study also revealed an extremely poor attenuation of maltose by T. delbrueckii YH178 and YH179, both of which eventually reached an alcohol content of approximately 0.3% (v/v) after 2 weeks of fermentation (Barry et al , ). In addition, the estimated ethanol contents based on the decreases in °Brix were significantly greater in Prelude (3.78, v/v) and Concerto (3.82, v/v)‐fermented beers than that of Biodiva‐fermented beers (1.33, v/v) (Table ).…”
Section: Ph Total Soluble Solids and Sugar Changes During Fermentationmentioning
confidence: 56%
“…Mead is a traditional alcoholic beverage (alcoholic strength, by volume, between 8 and 18%) produced by the fermentation by yeasts of diluted honey. The production of mead has been the focus of numerous studies . However, few reports consider the volatile profile of mead and even fewer consider the production and characterisation of sparkling mead.…”
Section: Introductionmentioning
confidence: 99%
“…In the present review, we explored available information on the biochemical, genomic and phenotypic features of T. delbrueckii, with special emphasis on the aspects that make this yeast a promising biotechnological model to be exploited in a wide range of industries, Yeasts from the genus Torulaspora have been reported in a wide variety of habitats, such as fruits [6], insects [7,8], soils [9], soil invertebrates [10], plants [11,12], seawater [13], spoiled food [6] and malt environments [6], where yeast from other genera like Saccharomyces and Zygosaccharomyces may also be present [14,15]. Although not considered a human pathogen, the species T. delbrueckii can also be found as a clinical isolate [16].…”
Section: Introductionmentioning
confidence: 99%